Different proximal and distal rearrangements of chromosome 7q associated with holoprosencephaly. Issue 11 (November 1997) - Benzacken, B; Siffroi, J P; Le Bourhis, C; Krabchi, K; Joyé, N; Maschino, F; Viguié, F; Soulié, J; Gonzales, M; Migné, G; Bucourt, M; Encha-Razavi, F; et al.
Abstract : Four new cases of holoprosencephaly are described in fetuses exhibiting abnormal karyotypes with different distal and proximal rearrangements of the long arm of chromosome 7. Three of them showed terminal deletions of chromosome 7q, confirming the importance of the 7q36 region in holoprosencephaly. The karyotype of the fourth fetus showed an apparently balanced de novo translocation, t(7;13) (q21.2;q33), without any visible loss of the distal part of chromosome 7q. The involvement of new genes, different from the human Sonic Hedgehog gene (hShh) responsible for holoprosencephaly, or a positional effect are discussed.